2014
DOI: 10.1002/smj.2313
|View full text |Cite
|
Sign up to set email alerts
|

Top management conservatism and corporate risk strategies: Evidence from managers' personal political orientation and corporate tax avoidance

Abstract: We investigate whether managers' personal political orientation helps explain tax avoidance at the firms they manage. Results reveal the intriguing finding that, on average, firms with top executives who lean toward the Republican Party actually engage in less tax avoidance than firms whose executives lean toward the Democratic Party. We also examine changes in tax avoidance around CEO turnovers and find corroborating evidence. Additionally, we find that political orientation is helpful in explaining top manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(257 citation statements)
references
References 89 publications
(159 reference statements)
7
244
0
6
Order By: Relevance
“…The results of this analysis are shown in Model 5 of Table and show that the new CEO's political orientation is negatively related to the pay mix of the prior CEO ( β = −.025, p = .006). Given that firms tend to hire executives with similar political orientation over time (Christensen et al, ), this finding suggests that new CEOs seem to be attracted to firms that offered the prior CEO a pay package that is consistent with the new CEO's risk preferences.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of this analysis are shown in Model 5 of Table and show that the new CEO's political orientation is negatively related to the pay mix of the prior CEO ( β = −.025, p = .006). Given that firms tend to hire executives with similar political orientation over time (Christensen et al, ), this finding suggests that new CEOs seem to be attracted to firms that offered the prior CEO a pay package that is consistent with the new CEO's risk preferences.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, research in political science suggests that an individual's political party identification is typically formed in early adulthood and remains relatively constant throughout life (Green, Palmquist, & Schickler, ). Consistent with this notion, Christensen et al (: p. 10) found that, “when executives' political orientation scores from individual election cycles were compared to their lifetime political orientation score, 92 percent of the time both scores were leaning toward the same political party.” Thus, rather than being a reflection of CEOs simply giving to the party in power, giving is quite stable over time.…”
Section: Political Orientation and Ceos' Initial Compensation Packagesmentioning
confidence: 94%
“…The negative publicity resulted in verbal attacks from members of Parliament, customer boycotts of Starbucks stores, significant drops in the firm's reputation ratings, and numerous store closures (Christensen et al. []). The reputational damage prompted Starbucks to voluntarily pay future taxes and relocate physical offices to the United Kingdom, even though the company had purportedly been in compliance with U.K. tax law (Titcomb []).…”
Section: Background and Hypothesismentioning
confidence: 99%
“…Differences in political ideology have been shown to have an important influence on thinking and actions, not only in people's daily lives (Jost, Federico, & Napier, ), but also in the decisions of organizational leaders. Recent work has examined how the political ideologies of executives and top managers influence their managerial and governance decisions and actions (Chin, Hambrick, & Trevino, ; Christensen, Dhaliwal, Boivie, & Graffin, ; Gupta & Wowak, ). Extending this perspective to the arena of financial misconduct, we propose that political ideologies may have an important influence on board members' key decisions and actions through two primary effects: ideo‐attribution and threat management.…”
Section: Theory and Hypothesismentioning
confidence: 99%